DIGITAL TECHNOLOGIES AND THE DEMANDS OF THE TIME - Elboyeva Vasila Kamoliddin qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article analyzes the importance of digital technologies in today’s society and economy, their application across various sectors, and their connection to modern demands. Digital technologies accelerate innovation, automate work processes, and enable effective data management. At the same time, their use requires new skills and competencies, making human resource development a pressing issue.